Primary renal mucosa-associated lymphoid tissue lymphoma coexisting with immune thrombocytopenia - Jiatai He; Changqi Deng; Yu Huang; Miao Wang; Chengcheng Wei; Feixiang Xu; Ruokang Chen; Junduo Wang; Ming Yang; Zhaohui Chen (World Journal of Surgical Oncology)
Abstract Background Primary renal mucosa-associated lymphoid tissue (MALT) lymphoma is exceedingly rare. Although immune thrombocytopenia (ITP) may accompany lymphoproliferative disorders, its association with primary renal MALT lymphoma has not been previously reported. Case presentation A 60-year-old male presenting with isolated thrombocytopenia was diagnosed with ITP during hematologic evaluation. Abdominal imaging incidentally revealed an 8.7 × 5.6 cm renal mass. Glucocorticoid therapy successfully stabilized platelet counts, enabling nephroureterectomy. Histopathological analysis demonstrated dense small lymphocyte infiltrates, with immunohistochemical confirmation of CD20 and Bcl-2 positivity establishing a diagnosis of MALT lymphoma. At six-month follow-up, the patient maintained disease-free status without adjuvant therapy. Conclusions We report a rare case of concurrent primary renal MALT lymphoma and ITP, achieving sustained remission through glucocorticoid therapy and surgical resection.